Experimental Study on Fibre-Reinforced Concrete Beam-Column Joint with Ductile Detailing Under Reverse Cyclic Loading - Das, Pallab; Choudhury, S (International Journal of Engineering and Technology, 2018)
The behaviour of a beam-column (BC) joint in a moment resisting framed structure is the key criteria when the structure is subjected to seismic loading. In the past many research have been carried out to grasp the mechanism of failure of beam-column joint and methods to enhance the performance of beam-column joint have been developed. The provision of ductile detailing as prescribed in IS-13920: 1993 has been followed. Improvement of the performance of joint region has been studied by using additional reinforcement with different fibres. In the present study the performance of the BC joint is studied in terms of load vs. displacement curve, stiffness degradation vs. drift angle curve and energy dissipation by the BC joint using different types of fibres in the specimen. The laboratory testing of the concrete cubes and cylinders reinforced with different percentages of fibre volume have been implemented. Based on the test results, the selection of the optimum quantity of fibre that can be used in beam-column joint for each type of fibre has been done. The testing of the specimens of BC joints is carried out in cyclic actuator of capacity 100 kN. The fibres which have been used in the present study are carbon fibre, steel fibre and glass fibre. Percentages of the fibres that had been added to the specimen are carbon fibre (0.75%), steel fibre (0.75%) and glass fibre (0.50%) respectively and the control specimen made from ordinary concrete made of M25 mix concrete. The performance of the specimens reinforced with different type of fibres is then compared and the specimen showing desirable performance under cyclic loading is found out. It has been observed that the application of carbon fibres could improve the strength and ductility of BC joints appreciably.Â Â